We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
177
1
avatar

help please

 Aug 28, 2018
 #1
avatar+7598 
+1

-3(y - 1)  =  9

                          First let's solve this equation for  y . Divide both sides by  -3 .

y - 1  =  9 / -3

 

y - 1  =  -3

                          Add  1  to both sides of the equation.

y  =  -3 + 1

 

y  =  -2

 

Now that we know  y  =  -2  ,   we can find the value of  \(\frac12\)y .

 

\(\frac12\)y  =  \(\frac12\)(-2)

 

\(\frac12\)y  =  -1

 Aug 28, 2018

25 Online Users

avatar